ANALISA EROSI DAN SEDIMEN BERBASIS SISTEM INFORMASI GEOGRAFIS PADA SUB DAS MIU SELAWESI TENGAH - Tandju, Indah Nur Alifa; Suhartanto, Ery; Dermawan, Very (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2019)
The quality of the Palu watershed, especially Miu Sub-watershed was decreased because of the existing land use change. Geological factors in the watershed also increased the level of sediment in the river. This problems decreased the quantity of fresh water that could be provided by using Saluki Weir. Therefore, the Miu Sub-Watershed needed to be carried out the calculation and estimation the location of erosion and sediments to plan the conservation pattern used vegetative method and mechanical methods. This study used the ArcSWAT 2012 model for erosion and sediment analysis. The simulation was conducted in 10 years (2008-2017), and calibration using 2017. The simulation results showed an average erosion value of 36.459 tons/ha/year and an average sediment value of 21202.33 m3. From the results of erosion and sediment obtained the critical level of Miu sub-watershed on critical potential criteria of 24274.83 ha (51.66% of watershed area), semi critical criteria 3809.09 ha (8.11% of watershed area), critical criteria 18871.4 ha (40.16% of watershed area), and super critical criteria of 37.43 ha (0.08% of watershed area). The result of conservation pattern by adjusted existing land has decreased level of erosion and sediment. Vegetative method decreased erosion average by 42.89% and average sediment by 42.60%. Effectiveness of the mechanical method using check dam is 31.99%.